Image-guided thermosensitive liposomes for focused ultrasound enhanced co-delivery of carboplatin and SN-38 against triple negative breast cancer in mice. (April 2021) - Cressey, Paul; Amrahli, Maral; So, Po-Wah; Gedroyc, Wladyslaw; Wright, Michael; Thanou, Maya
Abstract: Triggerable nanocarriers have the potential to significantly improve the therapeutic index of existing anticancer agents. They allow for highly localised delivery and release of therapeutic cargos, reducing off-target toxicity and increasing anti-tumour activity. Liposomes may be engineered to respond to an externally applied stimulus such as focused ultrasound (FUS). Here, we report the first co-delivery of SN-38 (irinotecan's super-active metabolite) and carboplatin, using an MRI-visible thermosensitive liposome (iTSL). MR contrast enhancement was achieved by the incorporation of a gadolinium lipid conjugate in the liposome bilayer along with a dye-labelled lipid for near infrared fluorescence bioimaging. The resulting iTSL were successfully loaded with SN-38 in the lipid bilayer and carboplatin in the aqueous core - allowing co-delivery of both. The iTSL demonstrated both thermosensitivity and MR-imageability. In addition, they showed effective local targeted co-delivery of carboplatin and SN-38 after triggered release with brief FUS treatments. A single dosage induced significant improvement of anti-tumour activity (over either the free drugs or the iTSL without FUS-activation) in triple negative breast cancer xenografts tumours in mice. Graphical abstract: Image 1